The effectiveness of non-pharmacological interventions in older adults with depressive disorders: A systematic review - Apóstolo, João; Bobrowicz-Campos, E.; Manuel Rodrigues; Inês Castro; Daniela Cardoso (International Journal of Nursing Studies, 2016)
Background It is widely acknowledged that mental health disorders are common in older adults and that depression is one of the most serious threats to the mental health of older adults. Although best practice guidelines point out that moderate to severe depression should be approached with pharmacotherapy together with complementary therapies, the use of antidepressant drugs in older adults has various disadvantages, such as long response time, side effects, potential risk of dependency and tolerance, poor compliance rates and high probability of drug interactions. In addition, qualitative studies of depressed people with a chronic illness have indicated that both patients and healthcare professionals prefer a psychosocial treatment for depression over a pharmacological one. Objective This review aimed to identify and synthesize the best available evidence related to the effectiveness of non-pharmacological interventions for older adults with depressive disorders. Design Systematic review of studies with any experimental design considering non-pharmacological interventions for older adults with depressive disorders. Data sources An initial search of MEDLINE and CINAHL was undertaken, followed by a second search for published and unpublished studies, from January 2000 to March 2012, of major healthcare-related electronic databases. Studies in English, Spanish and Portuguese were included in the review. Review methods This review considered studies that included adult patients, aged over 65 years with any type of depressive disorder, regardless of comorbidities and any previous treatments, but excluded those with manic or psychotic episodes/symptoms. All studies that met the inclusion criteria were assessed for methodological quality by two independent reviewers using a standardized critical appraisal checklist for randomized and quasi-randomized controlled studies from the Joanna Briggs Institute. Data extraction was also conducted by two independent reviewers based on the Joanna Briggs Institute data extraction form for experimental studies. Results Twenty-three studies met the inclusion criteria. Of those, seventeen were excluded after critical appraisal of methodological quality and six were included in this review. These studies included 520 participants and described cognitive behavior therapy, competitive memory training, reminiscence group therapy, problem-adaptation therapy, and problem-solving therapy in home care. Evidence suggests that all these interventions reduce depressive symptoms. Conclusions According to evidence, non-pharmacological interventions had positive effects on improving patients’ depression and may be useful in practice. However, due to the diversity of interventions and the low number of studies per intervention included in this systematic review, evidence is not strong enough to produce a best practice guideline.